2018
DOI: 10.1016/j.envres.2018.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Associations of urinary phthalate metabolites and lipid peroxidation with sperm mitochondrial DNA copy number and deletions

Abstract: Background: Phthalates, a chemical class of plasticizers, are ubiquitous environmental contaminants that have been associated with oxidative stress. Mitochondria DNA copy number (mtDNAcn) and DNA deletions (mtDNAdel) are emerging biomarkers for cellular oxidative stress and environment exposures. Objectives: To examine associations of urinary phthalate metabolite and isoprostane concentrations on sperm mtDNAcn and mtDNAdel in male partners undergoing assisted reproductive technologies (ART). Methods: Ninet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…For mtDNAcn and mtDNAdel quantification, we used a modified version of a previously published triplex qPCR method (Phillips et al, 2014;Huffman et al, 2018). In brief, a segment of the minor arc of the mtDNA was targeted for mtDNAcn assessment due to its stability within the genome, lack of interaction with other targets and high amplification efficiency.…”
Section: Sperm Mtdnacn and Mtdnadelmentioning
confidence: 99%
“…For mtDNAcn and mtDNAdel quantification, we used a modified version of a previously published triplex qPCR method (Phillips et al, 2014;Huffman et al, 2018). In brief, a segment of the minor arc of the mtDNA was targeted for mtDNAcn assessment due to its stability within the genome, lack of interaction with other targets and high amplification efficiency.…”
Section: Sperm Mtdnacn and Mtdnadelmentioning
confidence: 99%
“…The quanti cation of mtDNA 4977 DR and CN were assessed simultaneously using an e cient and effective multiplex real-time PCR assay, which makes our results reliable [17,18]. Additionally, the sample size of our study was larger than those of previous similar studies assessing the association between mtDNA CN and PCOS.…”
Section: Discussionmentioning
confidence: 91%
“…RNAse P (ThermoFisher, cat# 4403326) was chosen as the genomic DNA reference. The reaction components (given in nal concentrations) were as follows: 250 µM for mtMajArc probes and primers, 250 µM for mtMinArc probes and primers, and 1× concentration for RNAse P. Real-time PCR was performed at the same cycling conditions as previously described: 95 °C for 10 min for activation, followed by 40 cycles of 95 °C for 15 s, 55 °C for 15 s, and 60°C [17,18]. Three technical replicates were performed.…”
Section: Quanti Cation Of Mtdna Cn and Mtdna4977 Drmentioning
confidence: 99%
“…To our knowledge, this study is the first to evaluate the association between the mtDNA 4977 DR and PCOS. The mtDNA 4977 DR and mtDNA CN were measured simultaneously using an efficient and effective multiplex real-time PCR assay, making our results reliable ( 26 , 32 ). Additionally, the sample size in this study was larger than that reported in previous similar studies.…”
Section: Discussionmentioning
confidence: 94%